Rentabilidad financiera en la empresa “fundación de acción social del buen vivir” durante el período 2020-2021. - Gregor Narváez, Ariana Stephanya (2022)
This case study is based on the financial profitability of the company "FOUNDATION OF SOCIAL ACTION OF GOOD LIVING", which is a private company that is responsible for imparting knowledge of gastronomy, pharmacology, beauty, Barber Shop in the city. of Babahoyo, province of Los Ríos, in such a way that the company presents problems in the management of the financial profitability of the company. In fact, this case study is aimed at determining the main variables that originate due to poor management of profitability and investments within the company, using as a research technique an interview with the staff of the company "FOUNDATION OF SOCIAL ACTION DEL GOOD LIVING” and obtaining data to demonstrate the financial profitability and the return on equity that the company had in the periods 2020-2021. In this way to be able to identify the problem and solve it in a way in which you choose to take new ideas and new decisions for good organizational synergy. In this way, protect income by having better management and analyzing the current market through which the sector in which the company operates is going through, take care of the company by meeting the general and specific objectives in order to reach the vision that is has raised. Improving with the appropriate research and being able to rethink the future of the company with investments that can help its growth